1982
DOI: 10.1177/070674378202700811
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the MMPI forthe Differentiation of Suicidal and Non-Suicidal Depressions

Abstract: The MMPI profiles of forty suicidal and forty non-suicidal male and female depressed patients, matched for age, were compared. Significant differences between MMPI scale T scores which showed some sex specificity were found between the suicidal and non-suicidal depressives. These results replicate previous findings. However neither individual scale T scores, derived discriminant functions, nor actuarial or cluster analysis-derived MMPI profiles could completely discriminate between suicidal and non-suicidal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The higher scores obtained by both completers and attempters on the Mf scale is in keeping with what has been observed in previous studies (Kincel, 1983;Leonard, 1977;Waters et al, 1982;Watson et al, 1984). However, the scores on other scales are more surprising, as they suggest that attempters are more pathological than the others.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The higher scores obtained by both completers and attempters on the Mf scale is in keeping with what has been observed in previous studies (Kincel, 1983;Leonard, 1977;Waters et al, 1982;Watson et al, 1984). However, the scores on other scales are more surprising, as they suggest that attempters are more pathological than the others.…”
Section: Discussionsupporting
confidence: 89%
“…Although better results have been obtained in this regard, they nevertheless remain inconsistent (Clopton, 1978;Clopton & Baucom, 1979;Clopton & Jones, 1975;Clopton, Pallis, & Birtchnell, 1979;Clopton, Post, & Larde, 1983;Eyman & Eyman, 1991;Greene, 1988;Leonard, 1977;Stancak, Fraenkel, & Jassova, 1983;Waters et al, 1982). This could be due to the variety of samples used and to their respective heterogeneity, especially as regards gender (see Leonard, 1977), to the varying interval between MMPI administration and the suicidal acts (Clopton et al, 1983), and to the definition of the suicidal acts themselves (Watson et al, 1984).…”
Section: Use Of the Mmpi To Understand And Predict Suicidementioning
confidence: 87%
See 1 more Smart Citation
“…The findings of that study may have been influenced somewhat by the use of measures that have questionable psychometric characteristics. For instance, the outcome measure was the Minnesota Multiphasic Personality Inventory (MMP[) Suicide Threat Scale which some have suggested may not be valid (Clopton, 1978;Waters, Sendbuehler, Kincel, Boodoosingh, & Marchenko, 1982). Moreover, the measure of hopelessness was simply a 4-point rating of pessimism, rather than a standard measure of the construct.…”
Section: The Multidimensional Assessment Of Perfectionismmentioning
confidence: 99%
“…The highly suicidal and suicide completions were not significantly different but had lower K and Overcontrolled Hostility (OH) scores and higher Mf and D scores. Waters, et al (1982) also found that suicidal behavior was associated with significant Mf elevations above normal limits but the MMPI scores measured other factors than recent suicidal behavior. The MMPI did not satisfactorily distinguish suicidal and nonsuicidal depressed cases.…”
Section: Mental Illness and Personalitymentioning
confidence: 92%